Model Test Study on Cylindrical Blasting Stress Wave Propagation across Jointed Rock Mass with Different Initial Stresses - Qian Dong; XinPing Li; JunHong Huang (Advances in Civil Engineering)
In the drilling and blasting excavation of underground rock mass, the stress wave produced by the blasting holes usually propagates in the form of cylindrical wave, while the rock mass surrounding the underground engineering is initially subjected to the in situ stress. To explore the propagation and attenuation law of cylindrical stress wave in the in situ stressed rock mass, a model test of cylindrical blasting stress wave propagation across the intact and jointed rock mass under different initial stresses was carried out. First, the attenuation law of the cylindrical stress wave in the intact rock mass under different confining pressures is analysed, and then the influence of the confining pressure scales, the angle, and the number of joints on the propagation law of the cylindrical blast wave in the jointed rock mass is studied. The experimental results show that the physical attenuation of the cylindrical wave in the intact rock mass decreases and then increases as the confining pressure increases from zero. Under zero confining pressure, the transmission coefficient of the cylindrical wave in the jointed rock mass decreases with the increase of joint angle, and the transmission coefficient increases with the increase of the joint angle under confining pressure. As the confining pressure increases from zero, the transmission coefficient shows a trend of increasing firstly and then decreasing.